El arrecife de coral - Taylor, Barbara, 1954-; Burton, Jane (Madrid : Anaya, 1993)
Examines the variety of life found on coral reefs, including the seahorse, hermit crab, and sea slug.
Includes index.
Translation of : Coral reef.
900
Accelerated Reader AR
Reading Counts RC
Keywords: Coral reef animals -- Juvenile literature; Spanish language materials -- Juvenile literature